Prevalencia de brucelosis bovina en fincas ganaderas del cantón Pasaje - Villamar Martínez, Yamil Antonio (2014)
In order to determine the prevalence rate of bovine brucellosis in smallholder cattle farms cantón Pasaje provincia de EL Oro, to serological diagnosis, Card-Test, 500 cattle in parroquias, Progress, Tres Cerritos, Uzcurrumi and Buena Vista. For diagnosis proceeded to the extraction of blood from the coccygeal vein of each animal with a 5cc syringe to put it in a test tube were placed in an inclined manner to accelerate obtaining serum. Subsequently and by employing a capillary tube of the serum sample was taken and with another placing of the reagent in the aglutinoscopio while mixing with the aid of a toothpick, perform a circular motion; then waited 4 minutes, recommended as the optimum time for the reading of the sample. Were subjected 12% of the samples at random, to verification tests in the laboratory of Microbiology and Histopathology, Facultad de Agronomia de UTMACH. The results show a negative index of prevalence (0%) for B. abortus in the studied of farms Canton Pasaje.